Penerapan Matriks Pada Sistem Persamaan Linear Tiga Variabel (SPLTV) - Nurul Khofifah (PT PUSTAKA CENDEKIA GROUP, 2023)
The system of linear equations (SPL) is an equation that has a variable with the highest rank equal to 1. Before increasing the matrix in a three-variable system of linear equations, the determinant and inverse of the matrix must be determined first. Determine is the value that can be determined from the elements of a square matrix. If you know three linear equations with the form of three variables (x, y, and z), then you can arrange the main determinant, the determinant of the form of the variable x, the determinant of the form of the variable y, and the determinant of the form of the variable z. The inverse matrix is ​​an inverse of the second matrix. If the matrix is ​​multiplied it will produce a square matrix (AB = BA = I). In this article, we will explain how to apply matrices to a system of three-variable linear equations (SPLTV) using the Sarrus and Ajoin methods. Information collection methods used are library research and search engines. By applying the matrix to a three-variable linear equation system, students can find out how to calculate the determinant and inverse matrix in a three-variable linear equation system.